CPC-containing oral rinses inactivate SARS-CoV-2 variants and are active in the presence of human saliva. Issue 2 (18th February 2022) - Anderson, Enyia R.; Patterson, Edward I.; Richards, Siobhan; Pitol, Ana K.; Edwards, Thomas; Wooding, Dominic; Buist, Kate; Green, Alison; Mukherjee, Sayandip; Hoptroff, Michael; Hughes, Grant L.
Abstract : Introduction. The importance of human saliva in aerosol-based transmission of SARS-CoV-2 is now widely recognized. However, little is known about the efficacy of virucidal mouthwash formulations against emergent SARS-CoV-2 variants of concern and in the presence of saliva. Hypothesis. Mouthwashes containing virucidal actives will have similar inactivation effects against multiple SARS-CoV-2 variants of concern and will retain efficacy in the presence of human saliva. Aim. To examine in vitro efficacy of mouthwash formulations to inactivate SARS-CoV-2 variants. Methodology. Inactivation of SARS-CoV-2 variants by mouthwash formulations in the presence or absence of human saliva was assayed using ASTM International Standard E1052-20 methodology. Results. Appropriately formulated mouthwashes containing 0.07 % cetylpyridinium chloride but not 0.2 % chlorhexidine completely inactivated SARS-CoV-2 (USA-WA1/2020, Alpha, Beta, Gamma, Delta) up to the limit of detection in suspension assays. Tests using USA-WA1/2020 indicates that efficacy is maintained in the presence of human saliva. Conclusions. Together these data suggest cetylpyridinium chloride-based mouthwashes are effective at inactivating SARS-CoV-2 variants. This indicates potential to reduce viral load in the oral cavity and mitigate transmission via salivary aerosols.